Nationality as an Influential Variable with Regard to the Social Skills and Academic Success of Immigrant Students - Christian Fernández-Leyva; María Tomé-Fernández; José Manuel Ortiz-Marcos (MDPI AG, 2021)
This study aims to expand the existing scientific, theoretical and empirical knowledge about the influence of the variables age, gender, nationality and place of residence on the probability of developing social skills that generate social wellbeing, and, in addition, to identify the relationship between the most influential variable and the academic success of immigrant students. We hope that the educational community, in an intercultural context, can benefit from and apply this knowledge to assist immigrant students. In this study, a sample of n = 749 students aged between 12 and 18, of 41 different nationalities, is analyzed using the Social Skills Scale for Young Immigrants (SSSYI). Data analysis is performed with the SPSS and STATA statistical programs. Multiple linear regression (MLR) analyses verify that nationality is the most influential variable. In addition, when calculating the Pearson correlation, high and positive correlations are found between social skills, nationality and students' grades, with which academic success was measured. In conclusion, we find that students who emigrated from the European continent present better social skills, better social wellbeing and greater academic success.